Epicrates crassus SNAKE: COMPLETE MITOCHONDRIAL GENOME SEQUENCE - Lúcio, Nazaré; Miranda, Kelton; Larangote, Débora; Machado, Victor Hugo Martins; Kalapothakis, Evanguedes; Kalapothakis, Yan (Acta Biologica Brasiliensia, 2023)
Epicrates crassus Cope, 1862 is a snake distributed in South America and a target species for illegal animal trafficking. In this work, we sequenced and described this species complete mitochondrial genome sequence. The mtDNA of E. crassus has 17,379 bp, with 22 transfer RNA genes, 13 protein-coding genes, two ribosomal RNA genes, and two non-coding control regions. Phylogenetic reconstruction, based on the complete mitogenome sequence of E. crassus and 18 other mitogenomes, confirmed the best grouping of this species with other members of the Boidae family. These new data can contribute to correctly identifying E. crassus, which would represent one more tool in the fight against the illegal trafficking of this species.